2020
DOI: 10.1007/s00428-020-02747-2
|View full text |Cite
|
Sign up to set email alerts
|

A standardized postmortem protocol to assess the real burden of sudden infant death syndrome

Abstract: Sudden unexpected infant death (SUID) is a major cause of death in infants < 1 year of age. Sudden infant death syndrome (SIDS) is a SUID still unexplained after post-mortem examination. In 2014, a protocol of post-mortem investigation was introduced to assess both the prevalence and the etiopathogenesis of SUID. Our aim was to compare SUID data before and after the application of a standardized autopsy protocol of investigation. In the time interval 2004-2018, SUID cases occurring in the Veneto Region, NorthE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…Our data were obtained from the SUID case registry from 2009 to 2019. We found that gender, age of death, and seasonality were similar to those reported in a recent study carried out in Veneto, another Italian region [10], as well as those previously reported in other countries [11,12]. The seasonality shows a prevalence in autumn-winter similar to the other Italian study but it differs from that reported in more recent studies which show a spring/summer prevalence [13], while a winter prevalence occurred before the reduce the risk campaigns [14].…”
Section: Discussionsupporting
confidence: 89%
“…Our data were obtained from the SUID case registry from 2009 to 2019. We found that gender, age of death, and seasonality were similar to those reported in a recent study carried out in Veneto, another Italian region [10], as well as those previously reported in other countries [11,12]. The seasonality shows a prevalence in autumn-winter similar to the other Italian study but it differs from that reported in more recent studies which show a spring/summer prevalence [13], while a winter prevalence occurred before the reduce the risk campaigns [14].…”
Section: Discussionsupporting
confidence: 89%
“…In case of macroscopic gross findings or clinical history suggestive for other organs involvement, additional sampling is carried out several fields of human disease, particularly in the areas of cardiovascular diseases and infectious disease, allowing for instance significant progresses in the elucidation of pathogenetic mechanisms underlying sudden death [17], prion disease [18], Alzheimer disease [19], perinatal mortality [20], and sudden infant death syndrome [21]. The opportunity of performing postmortem examination of patients deceased for COVID-19 virus infection has raised significant concerns motivated by the potential risk of infectivity, to the extent that the Italian Ministry of Health has issued a recommendation that in principle tends to discourage from performing autopsies [6].…”
Section: Discussionmentioning
confidence: 99%
“…This increase in mortality rates may be due to excessive diagnosis without an exhaustive investigation of the underlying cause of death, including the analysis of the circumstances in which the death occurred, and the lack of an autopsy in the majority of cases. In addition, this may be due to inadequate training of forensic and medical staff and scarcity of human and economic resources ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…SIDS is defined as “the sudden unexpected death of an infant younger than one year of age, with onset of the fatal episode apparently occurring during sleep, that remains unexplained after a thorough investigation, including performance of a complete autopsy and review of the circumstances of death and the clinical history” ( 1 10 ).…”
Section: Introductionmentioning
confidence: 99%